2017
DOI: 10.5897/jahr2017.0422
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus and hepatitis B virus (HIV/HBV) co-infection in people living with HIV/AIDs identified in Yaound Central Hospital, Cameroon: Seroprevalence and impact on the disease progression

Abstract: Co-infection with HIV and hepatitis B virus (HBV) has become an important factor of co-morbidity and mortality. The aim of this study was to determine the seroprevalence of HIV/HBV co-infection and its effect on the disease progression in people living with HIV/AIDS identified in Yaoundé Central Hospital. Blood samples from 75 HIV positive patients were collected in Yaoundé Central Hospital from November 2015 to February 2016, for the determination of hepatitis B virus surface antigen (HBsAg) using immunoassay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Our finding was however lower than the findings of Iwolekun et al who reported 51.9% among HIV positive patients in Lagos [16] And that of Nwokedi et al with a much higher prevalence of 70.5% among HIV positive patients in Kano, Nigeria [17]. Other similar studies in Nigeria and parts of the world, reported lower prevalences such as 9.7% and 6.7% by Ejele et al and Okon et al in Nigeria while 16%, [18] 12.5% and 12.6% by Djuidje et al, Zoufaly et al [19] and Laop.…”
Section: Discussioncontrasting
confidence: 74%
“…Our finding was however lower than the findings of Iwolekun et al who reported 51.9% among HIV positive patients in Lagos [16] And that of Nwokedi et al with a much higher prevalence of 70.5% among HIV positive patients in Kano, Nigeria [17]. Other similar studies in Nigeria and parts of the world, reported lower prevalences such as 9.7% and 6.7% by Ejele et al and Okon et al in Nigeria while 16%, [18] 12.5% and 12.6% by Djuidje et al, Zoufaly et al [19] and Laop.…”
Section: Discussioncontrasting
confidence: 74%
“…HBV/HIV co-infection rates of 12.9% [18] and 16% [19] were reported in people living with HIV in Cameroon. Besides, HBV/HIV co-infection rates of 11.8% [20] and 3.1% [21] were reported in pregnant mothers in Nigeria and South Africa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…None of the pregnant mothers were co-infected with HBV and HCV [27,28]. Several studies were conducted to determine co-infection of HBV/HIV, HBV/ HCV, or HIV/HCV among the general population, general pregnant mothers, or HIV infected pregnant mothers [7,13,16,[18][19][20][21][22][23][24][25][26][27][28]. But, only a few studies have been conducted to determine co-infection of HIV or HCV and related risk factors among HBsAg positive delivering mothers globally and particularly in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…To date, Nigeria remains one of the endemic nations of the world whose citizen's health is being challenged with HBV and HIV infections and these viral diseases cause significant morbidity and mortality [6]. Although there are several reports of HBV/HIV co-infection in Nigeria [6,7,8], Nevertheless, for any control research work to be successful there is need for adequate information on the epidemiology of the disease including the population at risk. Considering this context, the present study was aimed to investigate the prevalence and determinants of hepatitis b virus among human immunodeficiency virus patients at a tertiary health care facility in Central Nigeria.…”
Section: Introductionmentioning
confidence: 99%